Democratization and the role of the military: Cases of Serbia and Tunisia - ElHusseiny, Mona Abdelmoneim (AUC Knowledge Fountain, 2019)
The 21st century witnessed two waves of uprisings, the Color Revolutions, which erupted in East Europe and the Arab Spring, during which the people took over the streets to demand their rights and freedoms, as well as, to oust their authoritarian rulers. Nevertheless, the outcomes of such uprisings varied considerably among the affected countries; while few were successfully able to witness a regime breakdown and a democratizing transition, others failed either to achieve a regime breakdown, or to follow a democratic transition following their regime's breakdown. Thus, this research investigated why some countries have succeeded to follow a democratizing transition after mass mobilization, while others failed? What is the role of the military in such transitions? The research focused on the two outliers, democratizing cases, emerging from the Colored revolutions and the Arab Spring, which are respectively, Serbia and Tunisia and argued that the successful democratizing cases of both revolutionary waves presented and shared two factors that were not, simultaneously, present in the other failed cases; first, the refrainment of the military to use coercive power and second, the disengagement of the military from the political sphere during the transition phase. The main findings of the study validated the hypothesis by showing that the presence of the two highlighted factors simultaneously in the studied cases was a precondition to their regime breakdown and democratizing transition and that the absence of these factors interrupts the transition towards democracy. Nevertheless, the importance or contribution of these factors to the latter outcome varied across the studied cases; while they consisted a crucial aspect that enabled democratization in Tunisia, they were complementary factors in Serbia, or in other words, they were as important as other preconditions to the democratization of Serbia. Consequently, the study emphasized that the two presented factors are not the only preconditions that enabled the democratization of the two cases; they were necessary but insufficient conditions, instead, they were accompanied by other factors that were as important and contributive to the outcome, or were accompanied by secondary preconditions, as in the case of Tunisia.